A multifunctional phase-change microcapsule and its preparation method and application

By using boron nitride lignin hybrids in phase change microcapsules, the problems of low thermal conductivity and lack of ultraviolet shielding function of existing phase change microcapsules are solved, and a multifunctional phase change microcapsules with high thermal conductivity and excellent ultraviolet shielding are achieved, which is suitable for the preparation of high-performance fabrics and coatings.

CN115746794BActive Publication Date: 2025-04-18FOSHAN UNIVERSITY

Patent Information

Application Number
CN202211310104.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-04-18
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The existing phase change microcapsules have problems such as low thermal conductivity, untight shell structure and lack of ultraviolet shielding during solid-liquid phase change, which limits their application in fabrics and coatings.

Method used

By using boron nitride lignin hybrid as a component of the Pickering emulsion, multifunctional phase change microcapsules with high thermal conductivity, high latent heat, dense shell structure and excellent ultraviolet shielding function are prepared.

Benefits of technology

The thermal conductivity and ultraviolet shielding performance of phase-change microcapsules are synergistically improved, the preparation process is simple, the raw materials are environmentally friendly, and suitable for the preparation of fabrics or coatings with ultraviolet shielding function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115746794B_ABST
    Figure CN115746794B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of phase change material microcapsules, and specifically discloses a multifunctional phase change microcapsule and its preparation method and application. First, an oil phase solution and a boron nitride lignin hybrid are prepared, and the prepared boron nitride lignin hybrid is dispersed in water and homogenized and emulsified with a water-soluble polyol and an oil phase solution to obtain a Pickering emulsion; in a nitrogen atmosphere, the mixture is heated to 50-80°C and stirred to react for a period of time, and after the reaction is completed, the multifunctional phase change microcapsule is obtained after suction filtration, washing, and drying. Compared with the prior art, the multifunctional phase change microcapsule prepared by the present invention has the characteristics of high thermal conductivity, high latent heat, compact shell structure, excellent ultraviolet shielding, etc., and can be used to prepare fabrics or coatings with ultraviolet shielding function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase change material microcapsules, in particular to a multifunctional phase change microcapsule and a preparation method and application thereof. Background Art

[0002] Phase change materials are environmentally friendly thermal energy storage materials that are widely used in building energy conservation, smart fabrics, electronic equipment heat dissipation and other fields, and have attracted widespread attention from academia and industry. Among them, organic phase change materials have become the most widely used in thermal management applications due to their advantages such as high latent heat value, easy molding, high cycle life, and corrosion resistance. However, in the solid-liquid phase change process, organic phase change materials have problems such as flow and leakage. Therefore, it is usually necessary to microencapsulate the phase change materials and prepare them into phase change microcapsules. Polymer materials have the characteristics of light weight, good stability and corrosion resistance, and are the preferred wall materials for preparing phase change microcapsules. However, it is well known that most polymer materials and organic phase change materials have low intrinsic thermal conductivity, and the time required for heat storage and heat release is long, and they are insensitive to heat and temperature changes; moreover, long-term endothermic and heat release cycles and external forces will cause the wall material to rupture and cause the phase change material to leak. Therefore, how to prepare phase change microcapsules with both high thermal conductivity and dense shell structure is of great research significance to improve the comfort and performance of fabrics. Usually, in order to improve the thermal conductivity of phase change microcapsules, high thermal conductivity fillers such as metals, graphene, carbon nanotubes, and boron nitride can be added. However, most metals are easily corroded, while graphene and carbon nanotubes have darker colors, which severely limits their application in light-colored products such as fabrics and coatings. Boron nitride is a light-colored filler with a two-dimensional lamellar structure. It has excellent intrinsic thermal conductivity, high stability, and corrosion resistance. In recent years, it has attracted widespread attention from researchers. However, unexfoliated hexagonal boron nitride has extremely high chemical inertness, making it difficult to form a uniform dispersion and a good thermal conductivity path in phase change microcapsules.

[0003] Chinese patent application No. 201610456325.X discloses a nano-thermal conductivity enhanced microcapsule composite phase change energy storage material and a preparation method thereof, wherein the nano-thermal conductivity enhanced material is a high thermal conductivity nanoparticle such as boron nitride (BN), carbon nanotube (CNT) or graphene oxide (GO), and the core material is an organic phase change energy storage material, wherein the added BN, CNT, and GO are all modified to contain hydroxyl groups. In addition, nano-thermal conductivity enhanced particles such as BN, CNT or GO can be added to the core material of the microcapsule at the same time according to actual needs. Although this solution can enhance the thermal conductivity of the phase change microcapsule, its function is limited to this. In addition, the invention requires additional emulsifiers to be added during the preparation process; the melamine resin used is relatively brittle, and the raw materials of the melamine resin require formaldehyde, which has certain hazards, and there are certain limitations on its application in the fields of fabrics and the like. On the other hand, studies have shown that long-term exposure to ultraviolet rays can cause sunburn, sagging and aging of the skin, and even skin cancer. In particular, since the beginning of the last century, the ozone layer above the earth has been severely damaged, and the ultraviolet rays reaching the surface have continued to increase, further seriously threatening human life and health. Therefore, for applications such as smart fabrics, it is necessary not only to improve their comfort through phase change microcapsules, but also to fully consider their ultraviolet shielding performance. In this context, how to prepare a thermally conductive enhanced phase change microcapsule with ultraviolet shielding function becomes particularly important. Lignin is the second largest natural polymer material in nature after cellulose. However, most of the lignin is currently used as a low-value-added fuel for heat recovery, resulting in serious waste of resources. Studies have shown that the functional groups such as phenolic hydroxyl groups on the surface of lignin and its highly aromatic ring characteristics give it good ultraviolet shielding, antioxidant and light stability. Compared with the currently commercialized ultraviolet shielding agents, lignin also has outstanding advantages such as natural, non-toxic, good biocompatibility, renewable, and good cell safety. However, there are few reports on the preparation of phase change microcapsules with ultraviolet shielding function using lignin. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a multifunctional phase change microcapsule and a preparation method and application thereof. The prepared multifunctional phase change microcapsule has the characteristics of high thermal conductivity, high latent heat, dense shell structure, excellent ultraviolet shielding, etc., and can be used to prepare fabrics or coatings with ultraviolet shielding function.

[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0006] The first object of the present invention is to provide a method for preparing a multifunctional phase-change microcapsule, comprising the following steps:

[0007] S1, dissolving 20-25 parts by weight of diisocyanate and 5-10 parts by weight of diol in 20-25 parts by weight of organic solvent, dropping 0.05-0.3 parts by weight of dibutyltin dilaurate, heating to 50-80° C. under nitrogen atmosphere, stirring and reacting for 1-3 hours, and then adding 80-120 parts by weight of organic phase change material to obtain an oil phase solution;

[0008] S2, dissolving 0.15-0.3 parts by weight of lignin in 250-400 parts by weight of sodium hydroxide solution, adding 1.5-8 parts by weight of hexagonal boron nitride, and ultrasonically treating for a period of time under stirring, washing the supernatant to neutrality after centrifugation, and drying to obtain a boron nitride lignin hybrid;

[0009] S3, dispersing the prepared boron nitride lignin hybrid into water to prepare 100 parts by weight of a 0.5 wt% to 5 wt% dispersion, adding 0.5 to 2 parts by weight of a water-soluble polyol, mixing evenly, adding 10 to 20 parts by weight of the oil phase solution prepared in step S1, homogenizing and emulsifying to obtain a Pickering emulsion;

[0010] S4. In a nitrogen atmosphere, heat to 50-80°C and stir to react for a period of time. After the reaction is completed, filter, wash and dry to obtain multifunctional phase change microcapsules.

[0011] As a preferred embodiment of the present invention, the organic solvent in step S1 is one or a combination of ethyl acetate, toluene, xylene, acetone and cyclohexanone.

[0012] As a preferred embodiment of the present invention, the organic phase change material in step S1 is one or a combination of n-octadecane, paraffin, and stearate.

[0013] As a preferred embodiment of the present invention, the pH value of the sodium hydroxide solution in step S2 is 12-15.

[0014] As a preferred embodiment of the present invention, the water-soluble polyol in step S3 is one or a combination of pentaerythritol, trimethylolpropane, glycerol and triethanolamine.

[0015] As a preferred embodiment of the present invention, the stirring rate in step S3 is 200-500 rpm, and the reaction time is 2-6 h.

[0016] The second object of the present invention is to provide a multifunctional phase-change microcapsule prepared by the above method.

[0017] The third object of the present invention is to provide a multifunctional phase change microcapsule for use in preparing fabrics or coatings with ultraviolet shielding function.

[0018] The principle of the present invention is that the phase change microcapsules are prepared by using a Pickering emulsion stabilized by a boron nitride-lignin hybrid, wherein the boron nitride-lignin hybrid is obtained by exfoliating hexagonal boron nitride with the assistance of alkali lignin. This hybrid has good dispersibility in water and can effectively improve the thermal conductivity of the phase change microcapsules. Moreover, the lignin component on the surface can play a good ultraviolet shielding role.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) Boron nitride has extremely high chemical inertness and is difficult to form an effective heat conduction path in phase change microcapsules, which seriously restricts the application of boron nitride in thermally conductive enhanced phase change microcapsules. The present invention uses lignin to assist in the exfoliation of boron nitride, achieving green and efficient exfoliation of boron nitride in water, avoiding the pollution problem existing in the exfoliation of boron nitride, and the prepared boron nitride-lignin hybrid can give full play to the thermal conductivity advantage of boron nitride and the ultraviolet shielding effect of lignin.

[0021] (2) Currently, there are few reports on microcapsules that have both UV shielding function and thermal conductivity enhancement performance, and achieving synergistic improvement of thermal conductivity and UV shielding performance of phase change microcapsules still faces certain challenges. Generally speaking, in order to improve the thermal conductivity of phase change microcapsules, it is often necessary to add a certain amount of thermally conductive filler, but most thermally conductive fillers have weak interface bonding with the polymer shell; moreover, a single thermally conductive filler cannot improve the UV shielding performance of the microcapsules, and another UV shielding agent needs to be added. The present invention utilizes boron nitride lignin hybrids directly for Pickering emulsion polymerization, which can achieve synergistic improvement of thermal conductivity and UV shielding performance of phase change microcapsules. The preparation process is simpler and easier, and can be used to prepare fabrics or coatings with UV shielding functionality.

[0022] (3) The raw materials used in the present invention are more environmentally friendly and have lower costs, which will effectively alleviate the double pollution problem existing in the current pulping and papermaking waste liquid and boron nitride liquid phase stripping, and has good ecological and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Digital photos and SEM images of the boron nitride-lignin hybrid prepared in Example 1: (a) digital photo; (b) SEM image.

[0024] Figure 2 The particle size distribution curve and SEM image of the multifunctional phase-change microcapsules prepared in Example 1: (a) particle size distribution curve; (b) SEM image.

[0025] Figure 3 This is the DSC curve of the multifunctional phase-change microcapsules prepared in Example 1.

[0026] Figure 4 This is the UV-visible spectrum of the multifunctional phase-change microcapsules prepared in Example 1.

[0027] Figure 5 This is the particle size distribution curve of the multifunctional phase-change microcapsules prepared in Example 2-5. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0029] Unless otherwise specified, the raw materials and reagents used in the following examples were purchased from the market, and their specific sources are not described in detail again.

[0030] Example 1

[0031] 25 g of isophorone diisocyanate and 5 g of polyethylene glycol were dissolved in 20 g of ethyl acetate, 0.3 g of dibutyltin dilaurate was dropped, and the mixture was heated to 60° C. and stirred for 1 h under a nitrogen atmosphere, and then 105 g of n-octadecane was added to obtain an oil phase solution; 0.2 g of lignin was dissolved in 300 g of a sodium hydroxide solution with a pH of 13, 3 g of hexagonal boron nitride was added, and the mixture was ultrasonically treated for 12 h under stirring, and the unpeeled boron nitride was removed by centrifugation. The obtained dispersion was centrifugally washed to neutrality, and then dried to obtain a boron nitride-lignin hybrid. The digital photos and SEM images of the prepared boron nitride-lignin hybrid are shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the prepared boron nitride lignin hybrid has a good two-dimensional lamellar structure, with a small amount of lignin nanoparticles bound to the surface; and the hybrid can be evenly dispersed in water to form a stable dispersion. Subsequently, the boron nitride lignin hybrid was re-dispersed in deionized water to prepare 100g of 0.7wt% dispersion, and then 15g of oil phase solution and 1g of trimethylolpropane were added. After stirring and homogenization, a stable Pickering emulsion was obtained; finally, in a nitrogen atmosphere, it was heated to 60°C, stirred and reacted at 300rpm for 2.5h, filtered and washed, and then dried in a vacuum oven at 60°C to obtain multifunctional phase change microcapsules based on boron nitride lignin hybrids. The particle size distribution curve and SEM image of the prepared multifunctional phase change microcapsules are shown in Figure 2. Figure 2 As shown, from Figure 2 From the particle size distribution curve, it can be seen that the average particle size of the phase change microcapsules prepared in this embodiment is 15.3 μm; it can withstand 10000 rpm centrifugation and has good mechanical strength of the shell; in addition, Figure 2It can be seen from the scanning electron microscope image that the microcapsules have regular shapes, and the size and particle size curves are basically consistent; moreover, it can be seen from the enlarged image that the boron nitride lignin hybrid is stably combined on the surface of the microcapsules to form a relatively rough surface structure, which has a good effect on improving the ultraviolet shielding performance and thermal conductivity of the microcapsules; Figure 3 It can be seen from the DSC curve that the melting and solidification temperatures of the phase change microcapsules are 27.2°C and 25.9°C respectively, and the melting enthalpy and solidification enthalpy are as high as 146.8J / g and 148.7J / g respectively; the thermal conductivity test results show that compared with the uncoated phase change material, the thermal conductivity is increased by 61% to 0.273W / mK.

[0032] Example 2

[0033] 20 g of toluene diisocyanate and 8 g of polytetrahydrofuran were dissolved in 20 g of toluene, 0.2 g of dibutyltin dilaurate was dropped, and the mixture was heated to 80° C. and stirred for reaction for 1 h under a nitrogen atmosphere, and then 80 g of n-octadecane was added to obtain an oil phase solution; 0.15 g of lignin was dissolved in 250 g of a sodium hydroxide solution with a pH of 12, 1.5 g of hexagonal boron nitride was added, and ultrasonic treatment was continued for 12 h under stirring, and the unstripped boron nitride was removed by centrifugation. The obtained dispersion was centrifugally washed to neutrality and dried to obtain a boron nitride-lignin hybrid. The boron nitride lignin hybrid was redispersed in deionized water to prepare 100g of 0.5wt% dispersion, and then 10g of oil phase solution and 0.5g of pentaerythritol were added, and a stable Pickering emulsion was obtained after stirring and homogenization; finally, it was heated to 60°C in a nitrogen atmosphere, stirred and reacted at 300rpm for 3h, filtered and washed, and then dried in a vacuum oven at 60°C to obtain multifunctional phase-change microcapsules based on boron nitride lignin hybrids. The average particle size of the phase-change microcapsules prepared in this embodiment is 14.5μm, and the particle size distribution curve is as shown in FIG. Figure 5 As shown; it can withstand 10000rpm centrifugal treatment and the mechanical strength of the shell is good; the melting and solidification temperatures of the phase change microcapsules are 27.1℃ and 25.6℃ respectively, and the melting enthalpy and solidification enthalpy are as high as 107.2J / g and 108.4J / g respectively; the thermal conductivity of the phase change microcapsules reaches 0.254W / mK, which is significantly better than that of pure phase change materials.

[0034] Example 3

[0035] 20 g of diphenylmethane diisocyanate and 5 g of polyethylene glycol were dissolved in 20 g of ethyl acetate, 0.05 g of dibutyltin dilaurate was dropped, and the mixture was heated to 50° C. and stirred for 3 h under a nitrogen atmosphere, and then 109 g of paraffin was added to obtain an oil phase solution; 0.2 g of lignin was dissolved in 300 g of sodium hydroxide solution with a pH of 15, 4 g of hexagonal boron nitride was added, and ultrasonic treatment was continued for 12 h under stirring, and the unpeeled boron nitride was removed by centrifugation. The obtained dispersion was centrifuged and washed to neutrality, and then dried to obtain a boron nitride lignin hybrid. The boron nitride lignin hybrid was redispersed in deionized water to prepare 100g of 0.82wt% dispersion, and then 20g of oil phase solution and 2g of glycerol were added and stirred to obtain a stable Pickering emulsion; finally, the mixture was heated to 50°C in a nitrogen atmosphere, stirred at 200rpm for 4h, filtered and washed, and then dried in a vacuum oven at 60°C to obtain multifunctional phase-change microcapsules based on boron nitride lignin hybrids. The average particle size of the phase-change microcapsules prepared in this embodiment is 16.8μm, and the particle size distribution curve is as shown in FIG. Figure 5 As shown; the melting enthalpy and solidification enthalpy of the phase change microcapsules are as high as 143.2 J / g and 144.5 J / g respectively; the thermal conductivity of the phase change microcapsules reaches 0.290 W / mK.

[0036] Example 4

[0037] 20 g of hexamethylene diisocyanate and 10 g of polypropylene glycol were dissolved in 20 g of ethyl acetate, 0.2 g of dibutyltin dilaurate was dropped, and the mixture was heated to 60° C. and stirred for reaction for 1 h under a nitrogen atmosphere, and then 115 g of n-octadecane was added to obtain an oil phase solution; 0.2 g of lignin was dissolved in 300 g of a sodium hydroxide solution with a pH of 13, 2.8 g of hexagonal boron nitride was added, and ultrasonic treatment was continued for 12 h under stirring, and the unstripped boron nitride was removed by centrifugation. The obtained dispersion was centrifugally washed to neutrality and dried to obtain a boron nitride-lignin hybrid. The boron nitride lignin hybrid was redispersed in deionized water to prepare 100g of 1.1wt% dispersion, and then 15g of oil phase solution and 1g of triethanolamine were added. After stirring and homogenization, a stable Pickering emulsion was obtained. Finally, the mixture was heated to 50°C in a nitrogen atmosphere, stirred and reacted at 500rpm for 6h, filtered and washed, and then dried in a vacuum oven at 60°C to obtain multifunctional phase-change microcapsules based on boron nitride lignin hybrids. The average particle size of the phase-change microcapsules prepared in this embodiment is 12.5μm, and the particle size distribution curve is as shown in FIG. Figure 5 As shown; it can withstand 10000rpm centrifugal treatment and the mechanical strength of the shell is good; after 100 hot and cold cycles, the melting and solidification enthalpies are still as high as 146.3J / g and 148.1J / g respectively; the thermal conductivity of the phase change microcapsule reaches 0.292W / mK.

[0038] Example 5

[0039] 25 g of dicyclohexylmethane diisocyanate and 9 g of polytetrahydrofuran were dissolved in 25 g of toluene, 0.3 g of dibutyltin dilaurate was dropped, and the mixture was heated to 60° C. and stirred for reaction for 1 h under a nitrogen atmosphere, and then 120 g of stearate was added to obtain an oil phase solution; 0.3 g of lignin was dissolved in 400 g of sodium hydroxide solution with a pH of 14, 5.5 g of hexagonal boron nitride was added, and ultrasonic treatment was continued for 12 h under stirring, and the unpeeled boron nitride was removed by centrifugation. The obtained dispersion was centrifuged and washed to neutrality, and then dried to obtain a boron nitride lignin hybrid. The boron nitride lignin hybrid was redispersed in deionized water to prepare 100g of 5wt% dispersion, and then 18g of oil phase solution and 1.2g of trimethylolpropane were added, and a stable Pickering emulsion was obtained after stirring and homogenization; finally, it was heated to 80°C in a nitrogen atmosphere, stirred and reacted at 300rpm for 2h, filtered and washed, and then dried in a vacuum oven at 60°C to obtain multifunctional phase-change microcapsules based on boron nitride lignin hybrids. The average particle size of the phase-change microcapsules prepared in this embodiment is 16.4μm, and the particle size distribution curve is as shown in FIG. Figure 5 As shown; it can withstand 10000rpm centrifugal treatment and the mechanical strength of the shell is good; the melting enthalpy and solidification enthalpy of the phase change microcapsule are as high as 145.1J / g and 144.8J / g respectively; the thermal conductivity of the phase change microcapsule reaches 0.382W / mK.

[0040] Example 6

[0041] The multifunctional phase-change microcapsules prepared in Example 1 were added to cotton fabrics. The UV-visible spectrum of the multifunctional phase-change microcapsules after being added to the cotton fabrics is shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that the fabric with 5% multifunctional phase change microcapsules added can shield nearly 97.6% of UVB and 81.3% of UVA, and has excellent ultraviolet shielding effect. It can be seen that the multifunctional phase change microcapsules prepared by the present invention have good application prospects in smart fabrics.

[0042] Example 7

[0043] The multifunctional phase change microcapsules prepared in Example 1 were dispersed in aqueous polyurethane, and after ultrasonic stirring for 2 hours, a coating with a thickness of 10 microns was prepared using an air spray gun; for comparison, a pure polyurethane coating was also prepared using the same process; UV-visible spectrophotometer testing showed that the pure polyurethane coating had high transparency, and compared with pure polyurethane, the polyurethane coating to which 10% of the multifunctional phase change microcapsules were added was light yellow in color, and its shielding rates in the UVB and UVA bands were 98.4% and 84.8%, respectively, further indicating that the multifunctional phase change microcapsules prepared by the present invention also have good application prospects in advanced coatings.

[0044] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a multifunctional phase-change microcapsule, characterized in that: The following steps are involved: S1, dissolving 20-25 parts by weight of diisocyanate and 5-10 parts by weight of diol in 20-25 parts by weight of organic solvent, dropping 0.05-0.3 parts by weight of dibutyltin dilaurate, heating to 50-80° C. under nitrogen atmosphere, stirring and reacting for 1-3 hours, and then adding 80-120 parts by weight of organic phase change material to obtain an oil phase solution; S2, dissolving 0.15-0.3 parts by weight of lignin in 250-400 parts by weight of sodium hydroxide solution, adding 1.5-8 parts by weight of hexagonal boron nitride, and ultrasonically treating for a period of time under stirring, washing the supernatant to neutrality after centrifugation, and drying to obtain a boron nitride lignin hybrid; S3, dispersing the prepared boron nitride lignin hybrid into water to prepare 100 parts by weight of a 0.5 wt% to 5 wt% dispersion, adding 0.5 to 2 parts by weight of a water-soluble polyol, mixing evenly, adding 10 to 20 parts by weight of the oil phase solution prepared in step S1, homogenizing and emulsifying to obtain a Pickering emulsion; S4. In a nitrogen atmosphere, heat to 50-80°C and stir to react for a period of time. After the reaction is completed, filter, wash and dry to obtain multifunctional phase change microcapsules.

2. The method for preparing the multifunctional phase-change microcapsules according to claim 1, characterized in that: The organic solvent in step S1 is one or a combination of ethyl acetate, toluene, xylene, acetone, and cyclohexanone.

3. The method for preparing the multifunctional phase-change microcapsules according to claim 1, characterized in that: The organic phase change material in step S1 is one or a combination of n-octadecane, paraffin, and stearate.

4. The method for preparing the multifunctional phase-change microcapsules according to claim 1, characterized in that: The pH value of the sodium hydroxide solution in step S2 is 12-15.

5. The method for preparing the multifunctional phase-change microcapsules according to claim 1, characterized in that: The water-soluble polyol in step S3 is one or a combination of pentaerythritol, trimethylolpropane, glycerol and triethanolamine.

6. The method for preparing the multifunctional phase-change microcapsule according to claim 1, characterized in that: The stirring rate in step S3 is 200-500 rpm, and the reaction time is 2-6 h.

7. A multifunctional phase-change microcapsule prepared by the method according to any one of claims 1 to 6.

8. Use of the multifunctional phase-change microcapsule as claimed in claim 7 in preparing fabrics or coatings with ultraviolet shielding function.

Citation Information

Patent Citations

  • Nano thermal conductivity enhanced microcapsule composite phase change material and preparation method thereof

    CN106085368A

  • Large-particle-size polyurethane phase change microcapsule and preparation method thereof

    CN111359554A

  • Preparation method of capsule wall hydrogen bond self-repairing type microcapsule phase change material

    CN111690376A

Cited By

  • Preparation method and application of high-sensitivity wide-temperature-range thermal camouflage anticorrosive coating

    CN120574525A